Motivation and experiences of dentists of primary care dental clusters in Hungary: a qualitative inquiry - Sztrilich, András; Túri, Gergő; Kaposvári, Csilla; Teller, Rita; Vingender, István (Frontiers in Oral Health, 2025)
BackgroundIn recent years, dental clusters and networks have been established in primary care in many countries to improve access to services for the population and develop cooperation between providers. In Hungary, the first dental clusters were established in 2021, and currently, one-third of dental practices have already joined a cluster. The study aimed to gather and analyze early experiences regarding the motivation of participation in primary care dental clusters and experiences of implementation.MethodsQualitative in-depth individual interviews with primary care dentists (n = 21). The study was designed to meet the COREQ criteria for reporting qualitative research. The research team members defined a purposive sample of interviewees. All interviews were conducted from March to April 2024. A qualitative content analysis method was used to analyze the interview transcripts. The WHO health system framework was chosen for the theoretical framework of the analysis.ResultsThe motivations for joining a dental cluster were financial reasons, professional development and knowledge exchange. Lack of information and distrust were barriers to joining the dental clusters. Different professional management practices have developed within the clusters. In the interviewees' opinion, the population's access to preventive dental services has not yet changed substantially under the new operational model. The portfolio of services offered by dental clusters could be expanded to include a range of types of care. Digital health technologies and innovative solutions should be developed and widely adopted.ConclusionsIn designing policy measures to promote the broader adoption of the dental cluster model, it is helpful to consider the different factors influencing dentists' decisions during implementation. Dental clusters can benefit the public and dentists, but further development of the model and improvement of the primary conditions for the operation of practices are essential.